2014
DOI: 10.1016/j.molonc.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ability of adjuvant tamoxifen‐benefit gene signatures to predict outcome of hormone‐naive estrogen receptor‐positive breast cancer patients treated with tamoxifen in the advanced setting

Abstract: To identify molecular markers indicative of response to tamoxifen and easily implemented in the routine setting, we recently reported three gene signatures that could stratify post-menopausal tamoxifen-treated, estrogen receptor-positive (ER+) patients according to outcome in the adjuvant setting. Here, we evaluated the predictive potential of the total of 14 genes included in the 3 gene signatures using 2 hormone-naïve Dutch ER+ cohorts of a total of 285 recurrent breast cancer patients treated with first-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
(59 reference statements)
0
14
0
2
Order By: Relevance
“…The clinical characteristics of the 285 patients [225 from Rotterdam (Erasmus University Medical Center) and 60 from Nijmegen (Radboud University Medical Center)] whose primary tumor specimens and data were used here have been described previously by Sieuwerts et al . ( 33 ). The protocol to study biological markers associated with disease outcome was approved by the medical ethics committee of the Erasmus University Medical Center (Rotterdam, Netherlands) (MEC 02.953); for Nijmegen, coded primary tumor tissues were used in accordance with the Codes of Conduct of the Federation of Medical Scientific Societies in the Netherlands ( www.federa.org/codes-conduct ).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical characteristics of the 285 patients [225 from Rotterdam (Erasmus University Medical Center) and 60 from Nijmegen (Radboud University Medical Center)] whose primary tumor specimens and data were used here have been described previously by Sieuwerts et al . ( 33 ). The protocol to study biological markers associated with disease outcome was approved by the medical ethics committee of the Erasmus University Medical Center (Rotterdam, Netherlands) (MEC 02.953); for Nijmegen, coded primary tumor tissues were used in accordance with the Codes of Conduct of the Federation of Medical Scientific Societies in the Netherlands ( www.federa.org/codes-conduct ).…”
Section: Methodsmentioning
confidence: 99%
“…The study design is depicted in Figure 1. Tissue processing, RNA isolation, complementary DNA synthesis, and RT-qPCR were performed and normalized using the d Cq method on the average of 3 reference genes (HMBS, HPRT1, and TBP) as described (21). All RNA samples that required more than 25 rounds of real-time PCR for detectable products of our 3 reference genes at a fixed input of 10 ng of total RNA and at a threshold of 0.1 were considered of insufficient quality and were excluded from further analysis.…”
Section: Human Breast Cancer Casesmentioning
confidence: 99%
“…Thus, early identification of such phenomena could be of clinical importance for patients that will present with early or late endocrine resistance. In this respect they subscribe to a number of studies which have identified gene signatures related to the outcome of breast cancer patients (Frasor et al., 2006; Karlsson et al., 2013; Loi et al., 2008; Ma et al., 2004; Sieuwerts et al., 2014; Sikora et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have advanced a 47 gene signature related to tamoxifen resistance: the top‐ranked selected genes were ESR1, MET, FOS, SNCG, IGFBP4, and BCL2; additionally, a reduced expression of ESR1/ERα, IGFBP4, SNCG, BCL2, and FOS in the relapsing group was observed (Vendrell et al., 2008). Contrariwise, in a recent study, a three‐gene signature (BCL2, BCAR3 and NAT1) was proposed as a molecular marker of adjuvant tamoxifen beneficial therapy (Sieuwerts et al., 2014). In our study, analysis of the first data set (Loi et al., 2008) revealed 21 genes, differentially expressed in relapsing over non‐relapsing patients; some of these genes and related to stemness.…”
Section: Discussionmentioning
confidence: 99%